A case report of squamous papilloma of the hard palate in a pediatric patient - Jaya A R; Nagarathna C; N Aishwarya (Wolters Kluwer Medknow Publications, 2020)
Oral squamous papillomas are benign proliferating lesions induced by human papillomavirus. These lesions are painless and slowly-growing masses. As an oral lesion, it raises concern because of its clinical appearance. These lesions commonly occur between age 30 and 50 years, and sometimes can occur before the age of 10 years. Oral squamous papilloma accounts for 8% of all oral tumors in children. Common site predilection for the lesion is the tongue and palate and may occur on any other surface of the oral cavity such as the uvula and vermilion of the lip. Here, we are presenting a case of squamous papilloma on the palate in a 9-year-old child.